Five-year outcome after pelvic floor reconstructive surgery: evaluation using dynamic magnetic resonance imaging compared to clinical examination and quality-of-life questionnaire - Alt, Céline D.; Benner, Laura; Mokry, Theresa; Lenz, Florian; Hallscheidt, Peter; Sohn, Christof; Kauczor, Hans-Ulrich; Brocker, Kerstin A. (Acta radiologica, 2018)
Background Dynamic magnetic resonance imaging (dMRI) captures the entire pelvis during Valsalva maneuver and helps diagnosing pelvic floor changes after reconstructive surgery ...
Gesehen am 08.05.2020